Enhanced Energetic Electron Fluxes at the Region of the Auroral Oval During Quiet Geomagnetic Conditions November 2009 - Stepanova, M (2012)
Enhanced fluxes of subrelativistic electrons were studied using the CORONAS-PHOTON satellite data during November 2009. During this time interval quiet geomagnetic conditions were unusually quiet. It was found that for more than 50% of all events, the enhanced fluxes with very similar characteristics were observed at two or more consecutive orbits, i.e. have a life time of a few hours. The analysis of relative location of enhanced fluxes and auroral particle precipitations, measured simultaneously by the low orbiting METEOR-M and DMSP satellites, showed that the enhanced fluxes are located inside the auroral oval, i.e. poleward from the external boundary of the outer electron radiation belt. This fact was also confirmed comparing these fluxes with the auroral oval boundaries provided by the OVATION model of auroral precipitations. The nature of the observed events is discussed. © 2012 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Low orbiting satellite measurements; Subrelativistic electrons; Outer radiation belt; Auroral particle precipitations